2014
DOI: 10.1186/1129-2377-15-12
|View full text |Cite
|
Sign up to set email alerts
|

Headstrong intervention for pediatric migraine headache: a randomized clinical trial

Abstract: BackgroundThe purpose of this study was to evaluate the efficacy of a self-guided CD-ROM program (“Headstrong”) containing cognitive-behavioral self-management strategies versus an educational CD-ROM program for treating headaches, headache-related disability, and quality of life.MethodsParticipants were 35 children ages 7–12 years with migraine recruited from one university medical center and two children’s hospital headache clinics. Participants were randomly assigned to complete the Headstrong or educationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
90
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(90 citation statements)
references
References 30 publications
0
90
0
Order By: Relevance
“…Currently, there is limited research examining the efficacy of remotely delivered behavioral interventions for youth with headache. In several pilot trials of CBT delivered via audio tapes, CD‐ROM, and telephone, remotely delivered therapies have demonstrated preliminary efficacy in improving headache outcomes (e.g., headache days, intensity) and physical functioning among youth with headache . Results pertaining to the efficacy of Internet CBT in pediatric headache are mixed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there is limited research examining the efficacy of remotely delivered behavioral interventions for youth with headache. In several pilot trials of CBT delivered via audio tapes, CD‐ROM, and telephone, remotely delivered therapies have demonstrated preliminary efficacy in improving headache outcomes (e.g., headache days, intensity) and physical functioning among youth with headache . Results pertaining to the efficacy of Internet CBT in pediatric headache are mixed.…”
Section: Introductionmentioning
confidence: 99%
“…In several pilot trials of CBT delivered via audio tapes, CD-ROM, and telephone, remotely delivered therapies have demonstrated preliminary efficacy in improving headache outcomes (e.g., headache days, intensity) and physical functioning among youth with headache. [17][18][19] Results pertaining to the efficacy of Internet CBT in pediatric headache are mixed. A few studies of Internet CBT in youth with mixed chronic pain conditions including headache have shown efficacy compared to standard medical care in reducing headache pain intensity and activity limitations, 20,21 but benefits were not found in other areas such as depression, parent behaviors, or sleep.…”
Section: Introductionmentioning
confidence: 99%
“…29,32,39 In 2 trials, participants were assigned to either CBT plus amitriptyline or a headache education program plus amitriptyline, 28,39 whereas in the other 3 studies the intervention group was compared with a headache education program or control group. The headache education programs basically served as control group and were either provided by skilled professionals or with a CD-ROM (Rapoff et al's study), 33 and covered contents on general headache education, including triggers, and management of pharmacological therapies. CBT yielded a significant headache frequency reduction that ranged between 35.8% and 71.9% in 3 studies, 29,31,38 whereas Rapoff and colleagues did not find a significant headache frequency reduction (although the reduction was sizeable, ie, 47.9%, which was likely due to the small sample size).…”
Section: Resultsmentioning
confidence: 99%
“…11,18,59 Third, and specifically addressing one of the patients' most frequent objections, the behavioral treatments discussed above are absent the side effects and contraindications that are often associated with certain pharmacological prophylactic treatments. 28,[31][32][33][34][35][36]62 The joint effect of these factors may reduce clinical symptoms by enhancing the way in which patients experience pain perception and intensity. As research progresses we are learning that no single causative effect is sufficient.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies suggest that nonmedical therapy is an important component of care, particularly in patients with significant disability due to headache . Interventions to identify and address psychosocial stressors, education on behavioral management of headache triggers, and biobehavioral therapies (including cognitive behavioral therapy) have been used with success in young headache patients either as a primary therapy or as an adjunct to medical therapy . Studies in adult headache patients have demonstrated improved clinical outcomes and decreased resource utilization when headache education and other biobehavioral therapies are incorporated into standard care .…”
Section: Introductionmentioning
confidence: 99%